Vietnam urbanization review : (The World Bank (WB), 2011)
As Vietnam enters a crucial period of urbanization corresponding to its present stage of economic development, the Government of Vietnam has placed strong emphasis on developing its system of cities. In accordance with this objective this Urbanization Review is dedicated to understanding the key dimensions and aspects of Vietnam's urbanization process and to identifying trends, opportunities, challenges and core policy priorities that the government will need to address in order to realize its objective.